Women’s Reproductive Health Rights in Poland. Between a Druggists’ Conscience Clause and Their Legal Duty to Provide Contraceptives - Ciereszko, Kinga; Napiwodzka, Karolina; Nowak, Ewa; Hemmerling, Kay (ETHICS IN PROGRESS, 2023)
This article recommends the promotion of moral competence in the health and pharmacy professions to enable them to respect human and patient health rights with a focus on the provision of reproductive and sexual health care services. In certain cultures, health care and drug providers follow their conscientious objection (conscience clause) and decline to perform specific health services, including the provision of legal contraceptives in cases protected by legal and human rights. Such malpractices may violate patients’ and purchasers’ legitime rights. The article also presents findings obtained in Poland with N=121 women experimentally interviewed to examine their experiences as contraception purchasers, to assess their preference concerning facing human vs. robotic pharmacists, to manage the risk of refusal argued by the conscientious objection, and to score their moral competence with one of the dilemmas included in the MCT by G. Lind. This study demonstrated that purchasers with higher C-score (C for moral competence) would not just prefer a robotic pharmacist without a ‘conscience’ but, rather, a competent sales staff able to instruct the patient and advice her on any related queries. It further results that participants with higher moral competence are thus less likely to trust the medical expertise of artificial intelligence. We conclude that public institutions in pluralistic societies must manage normative reproductive health contexts more inclusively, and the election, education, and practice of health professionals in the public health care sector require the development of a normative mindset toward respecting the rights of all patients instead of respecting them selectively at the diktat of particularistic conscience.